Phenotypic and genotypic characteristics of pathogenic bacteria Aeromonas veronii bv veronii causes disease in gourami (Osphronemus gouramy) - DINI SISWANI MULIA; ZAHROTUN NISA; SUWARSITO SUWARSITO; CAHYONO PURBOMARTONO; ALIM ISNANSETYO; NUNAK NAFIQOH; INA SALWANY MD YASIN; MOHAMAD AZZAM-SAYUTI (Society for Indonesian Biodiversity, 2024)
Abstract. Mulia DS, Nisa Z, Suwarsito, Purbomartono C, Isnansetyo A, Nafiqoh N, Yasin ISM, Azzam-Sayuti M. 2024. Phenotypic and genotypic characteristics of pathogenic bacteria Aeromonas veronii bv veronii causes disease in gourami (Osphronemus gouramy). Biodiversitas 25: 5103-5111. Gourami (Osphronemus gouramy) is a type of freshwater fish with excellent potential, but its cultivation is often disturbed by bacterial diseases caused by Aeromonas spp. The presence of virulent genes often influences the pathogenicity of Aeromonas spp. and treatment with antibiotics causes bacteria resistance. Therefore, this study aimed to determine the phenotypic and genotypic characteristics of Aeromonas veronii bv veronii causing disease in gourami (O. gouramy). A purposive sampling method was used to obtain specific diseased gourami. Phenotypic characteristics were determined morphologically and biochemically, while genotypic characteristics were based on 16S rDNA and virulent genes. A total of 10 virulent genes were used, including the aerA/haem, alt, ast, act, flaA, lafA, fstA, ahp, ela, and lip genes. Subsequently, antibiotic susceptibility tests were carried out using 10 µg gentamycin disk, 10 µg bacitracin, 30 µg tetracycline, and 30 µg chloramphenicol. Data on phenotypic and genotypic identification, the detection of virulence genes, and antimicrobial susceptibility tests were analyzed descriptively and qualitatively. The results showed that isolate BmSG-03 was closely related to A. veronii bv veronii strain ATCC 35624 with a similarity rate and query of 99.58% and 100%, respectively. The A. veronii bv veronii BmSG-03 isolate was detected to contain the aerA/haem, lafA, and ela genes, while the alt, ast, act, flaA, fstA, ahp, and lip genes were not detected. This isolate was resistant to bacitracin, tetracycline, and gentamycin but susceptible to chloramphenicol. Moreover, further investigations were recommended on genotypic characteristics of A. veronii bv veronii resistance gene and other antibiotic tests due to limited reports in Indonesia. For effective disease control, there should be a comprehensive database on the characteristics of the pathogen to obtain more effective and appropriate mitigation efforts.